Período de carência de medicamento veterinário em tecidos comestíveis de origem animal - Guiraldelli, Giulia Gumiero [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The use of veterinary drugs in production animals may generate residues in their tissues, which can be harmful to human health. In order to ensure that the concentration of these residues does not exceed the Maximum Residue Limit (MRL), which is a safe limit, it is necessary to establish a withdrawal period, which can be defined as the waiting period of time so that an animal can be slaughtered after being treated with a veterinary drug. The calculation of this period takes place through the execution of clinical studies, the marker residue depletion studies, within the pharmaceutical company that owns such drug. The estimation of the withdrawal period is normally obtained by the fitting of a simple linear regression model, followed by the calculation of a tolerance limit. There are statistical assumptions that must be met for this method of choice to be used, but this is not always the case. Thus, when it is not possible to use linear regression, an alternative approach is chosen, which, in addition to establishing the withdrawal period at the time when residue concentrations in all tissues of all animals are equal or below the respective MRL, also makes use of a safety interval in order to compensate for the uncertainties inherent in various parameters

O uso de medicamentos veterinários em animais de produção pode gerar resíduos em seus tecidos, os quais podem ser prejudiciais à saúde humana. Como forma de garantir que a concentração de tais resíduos não exceda o Limite Máximo de Resíduo (LMR), que é um limite seguro, deve ser calculado o período de carência, que pode ser definido como intervalo de tempo que deve ser respeitado para que um animal possa ser abatido após ter sido tratado com certo medicamento veterinário. O cálculo desse período se dá pela execução de estudos clínicos de depleção de resíduos, dentro da empresa farmacêutica detentora de tal medicamento. A estimativa do período de carência usualmente é feita pelo ajuste de um modelo de regressão linear simples, seguido pelo cálculo de um limite de tolerância. Existem pressupostos estatísticos que devem ser atendidos para que esse método de escolha possa ser utilizado, porém nem sempre isso ocorre. Assim, quando não é possível fazer o uso da regressão linear, opta-se por uma abordagem alternativa, a qual além de estabelecer o período de carência no momento em que as concentrações de resíduos, em todos os tecidos de todos os animais, estão iguais ou abaixo dos respectivos LMR, também faz uso de um intervalo de segurança, a fim de compensar as incertezas inerentes a diversos parâmetros.
Veterinary drugs withdrawal period for edible tissues of food producing animals
Keywords: Medicamento veterinário; Resíduos; Período de carência; Veterinary drugs; Residues; Withdrawal period